2014
DOI: 10.1080/02772248.2014.907901
|View full text |Cite
|
Sign up to set email alerts
|

The effect of vitamin E supplementation on ovary and testis histopathology inOreochromis niloticusexposed to deltamethrin

Abstract: The effects of deltamethrin on the histology of Oreochromis niloticus testis and ovary and the protective effect of vitamin E supplementation were investigated. The fish were divided into four groups, i.e. a control group, a vitamin-E-treated group, a deltamethrin-treated group and a vitamin Eþdeltamethrin-treated group. In the control and vitamin-E-treated groups, the ovaries and testes were normal at the end of 7, 14, and 21 days. In the deltamethrin-treated group, deformed oocytes, atretic oocytes, melanoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…In this experiment, among the high significance alterations of factor (3), the atresic pre-ovulatory follicles identified at 56 days after exposure, are the most frequently observed alterations with higher values occurring in females exposed to Acer 35 EC. An increase in atresia was also observed in African catfish exposed to endosulfan (Agbohessi et al, 2015a), in Nile tilapia exposed to deltamethrin (Bayar et al, 2014), in Mozambique tilapia exposed to DDT (Mlambo et al, 2009), and in goldfish exposed to atrazine (Span o et al, 2004). Several authors have shown ovarian regression in fish treated with estrogenic pesticides (Pieterse et al, 2010;Mlambo et al, 2009;Span o et al, 2004).…”
Section: Histopathology Of the Liver Kidney And Gonadsmentioning
confidence: 97%
“…In this experiment, among the high significance alterations of factor (3), the atresic pre-ovulatory follicles identified at 56 days after exposure, are the most frequently observed alterations with higher values occurring in females exposed to Acer 35 EC. An increase in atresia was also observed in African catfish exposed to endosulfan (Agbohessi et al, 2015a), in Nile tilapia exposed to deltamethrin (Bayar et al, 2014), in Mozambique tilapia exposed to DDT (Mlambo et al, 2009), and in goldfish exposed to atrazine (Span o et al, 2004). Several authors have shown ovarian regression in fish treated with estrogenic pesticides (Pieterse et al, 2010;Mlambo et al, 2009;Span o et al, 2004).…”
Section: Histopathology Of the Liver Kidney And Gonadsmentioning
confidence: 97%
“…Staicu et al [23] determined that there was a decrease in sperm count in Corassius auratus gibelio exposed to deltamethrin for 14 days. In a study conducted by Bayar et al [24], it was stated that deltamethrin had adverse effects on the testicular tissue in Oreochromis niloticus, such as a decrease in the number of spermatogenic cells and structural deterioration in spermatogonia. It was observed that the adverse effects of deltamethrin on testicular tissue was more than tau-fluvalinate.…”
Section: Discussionmentioning
confidence: 99%
“…VC also recovers chick embryo from CPM-induced developmental anomalies (Sharma et al 2018d). Supplementation of VC potentially mitigates the reproductive toxicity also; it restores the histopathological changes in ovary and testis (Sharma et al 2011;Bayar et al 2014). Pretreatment of VC against insecticide-induced oxidative stress shows better protective effects than the posttreatment.…”
Section: Nutritional Supplementsmentioning
confidence: 99%